TEORI BELAJAR KOGNITIF DAN IMPLIKASINYA DALAM PEMBELAJARAN - Rahma Yanti; Dafirsam; Hidayani Syam (ADIBA : JOURNAL OF EDUCATION, 2024)
Education is the process of changing the attitudes and behavior of a person or group of people in an effort to mature humans through teaching and training efforts, educational processes, methods and actions. The theory underlying education is basically divided into association theory which is inductively oriented, meaning that the building of knowledge in educational development is based on units of knowledge, attitudes and skills into more universal units. The flow in this theory is behaviorism or better known as the stimulus-response flow. The school of thought that education is directed at creating new behaviors in students. Learning is an important part that cannot be separated from the educational process. Learning is a process of changing behavior and thought patterns experienced by individuals. Cognitive learning theory emphasizes that what is most important in the learning process is the implementation of how the process occurs rather than the results achieved.